2008
DOI: 10.1159/000128172
|View full text |Cite
|
Sign up to set email alerts
|

High Tie of the Inferior Mesenteric Artery in Curative Surgery for Left Colonic and Rectal Cancers: A Systematic Review

Abstract: Background: During surgery for left colonic and rectal cancers, the inferior mesenteric artery (IMA) can be ligated either at its aortic origin (high tie) or below the origin of the left colic artery (low tie). There is no consensus as to which method should be employed. Methods: We searched Medline, EMBASE, Cochrane collaboration, and National Guidelines Clearinghouse databases and undertook a systematic review on the use of IMA high tie during curative resections for left colonic and rectal cancers and its i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
109
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(117 citation statements)
references
References 91 publications
3
109
1
2
Order By: Relevance
“…Several reviews18, 19, 20, 21 found no significant difference between high and low tie with regard to short‐ and long‐term results, with different authors recommending different methods. All emphasized the need for RCTs18 20, 21. In the present study, patients with rectal cancer were randomized between high‐ and low‐tie ligation.…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews18, 19, 20, 21 found no significant difference between high and low tie with regard to short‐ and long‐term results, with different authors recommending different methods. All emphasized the need for RCTs18 20, 21. In the present study, patients with rectal cancer were randomized between high‐ and low‐tie ligation.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the oncological, technical and anatomical considerations, the position of ligation of the IMA has been debated on performing "high ligation" and "low ligation" in surgeries for the tumor of left colon and rectum (Lange et al, 2008;Titu et al, 2008;Cirocchi et al, 2012). Though there is still no consistent evidences of the survival benefits (Hida and Okuno, 2013), it is proved that high ligation of the IMA may improve lymph node removal rates (Adachi et al, 1998), accuracy of tumor staging (Titu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Though there is still no consistent evidences of the survival benefits (Hida and Okuno, 2013), it is proved that high ligation of the IMA may improve lymph node removal rates (Adachi et al, 1998), accuracy of tumor staging (Titu et al, 2008). Though high ligation of the IMA causes a reduction of blood supply to distal colon (Seike et al, 2007;Tsujinaka et al, 2012), it simultaneously contributes to low anastomosis with no tension in low anterior resection of rectal cancer Hida and Okuno, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review by Titu L V et al [21] concluded high ligation of the IMA can be performed safely and does not represent a source of increased morbidity in surgery for rectal and left colonic cancers. High tie leads to improved lymph node harvest, thus facilitating accurate tumour staging.…”
Section: A) Mechanical Bowel Preparationmentioning
confidence: 99%